The utilization of local agent knowledge by multinational MedTech firms in Emerging Markets Internationalization : a dynamic capabilities perspective - Olivier, Johan (University of Pretoria, 2023)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2022.